PEREMPUAN BALI DALAM DUA CERITA PENDEK:SELIR SULANDRIKARYA I MADE IWAN DARMAWAN DANKAUNG BEDOLOT KARYA GEDE ARIES PIDRAWAN(SEBUAH KAJIAN ETNOGRAFI KOMUNIKASI) - Nyoman Deni Wahyudi; Dewa Gede Bambang Erawan (Jurnal Santiaji Pendidikan (JSP), 2017)
This research is a descriptive qualitative research which aims to (1) find out the descriptions of Balinese women in Sulandri's concubine by I Made Iwan Darmawan which is studied based on the study of communication ethnography and (2) to know the description of Balinese women in the short story of Kaede Bedolot by Gede Aries Pidrawan, study of ethnographic communication. Sources of data in this study are two short stories of Sulandri's concubine by I Made Iwan Darmawan and Kaung Bedolot by Gede Aries Pidrawan which contains the description of Balinese women figure. The research method used is documentation study method. Processing or data analysis is done through data reduction, data presentation, conclusion drawing, and verification of research data. This research will provide the description of Balinese women in two short stories and has the benefit of being a learning media in the lectures, enriching the material of literary analysis, and enriching the treasury of critical discourse analysis, art, and culture of Indonesia especially Bali. The results of this study indicate that in the work of short story (short story) Selir Sulandri by I Made Iwan Darmawan who studied based on the study of communication ethnography, Balinese women described as women who follow patrilineal lineage, high social position, forced to marry early for the social and political status of the family , to experience polygamy, to impinge on the sexual desires of men (kings / husbands), jealousy, envy, gossip, and possessive jealousy, subjugation to men's power, discrimination, courage in the midst of situations critical, and must be willing to perform mesatia ritual. In the short story of Kaung Bedolot by Gede Aries Pidrawan, the figure of Balinese women is described not as different as that of wanting a coveted marriage, having polygamy, following patrilineal lineage, being forced to marry early for the social and political status of the family, doing housework, resigned and sincerely accepting fate, become victims of domestic violence, be brave in the middle of a discouraging situation, and end up with deaths from domestic violence. The result of this research is useful both theoretically and practically for students, lecturers, literature lovers, and education. Other researchers are expected to conduct further research in more depth.